2016
DOI: 10.3340/jkns.2016.59.6.655
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Spinal Revision Surgery in a Patient with Parkinson's Disease

Abstract: Parkinson's disease (PD) patients frequently have several spinal deformities leading to postural instabilities including camptocormia, myopathy-induced postural deformity, Pisa syndrome, and progressive degeneration, all of which adversely affect daily life activities. To improve these postural deformities and relieve the related neurologic symptoms, patients often undergo spinal instrumentation surgery. Due to progressive degenerative changes related to PD itself and other complicating factors, patients and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…A high rate of revision (31.9 ± 29.1%; range: 25.8–100%) following instrumentation of the the thoracolumbar spine is described in the literature. 8 9 10 11 12 13 In our retrospective case-control study, we found a comparatively high rate of revision (43.8%) for PD patients. Concerning indications of revision surgery, we found hardware failure (57.1%) to be the most frequent, a finding in accordance with former studies (47.4 ± 36.5%; range: 0–100%).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A high rate of revision (31.9 ± 29.1%; range: 25.8–100%) following instrumentation of the the thoracolumbar spine is described in the literature. 8 9 10 11 12 13 In our retrospective case-control study, we found a comparatively high rate of revision (43.8%) for PD patients. Concerning indications of revision surgery, we found hardware failure (57.1%) to be the most frequent, a finding in accordance with former studies (47.4 ± 36.5%; range: 0–100%).…”
Section: Discussionmentioning
confidence: 59%
“…3 4 5 6 7 The management of osteoporosis in patients undergoing spine surgery is challenging—unsurprisingly, many authors found osteoporosis to be an unfavorable comorbidity in PD patients who underwent spine surgery. 2 8 12 15 16 17 Among our PD cohort, 62.5% had BMD < 100 HU, which we defined as osteoporosis: eight patients with osteoporotic fractures 18 (OF III n = 1, OF IV n = 7), one patient with a traumatic fracture 19 (A3), and two patients with degenerative spondylolisthesis (Meyerding I). Kawaguchi et al 10 reported the case of a 67-year old woman with osteoporotic fractures of L4 and L5 who developed a new fracture of L1 6 months after initial vertebral body replacement (VBR) and instrumentation from L1 to S1, resulting in an extension of the instrumentation to T4.…”
Section: Discussionmentioning
confidence: 99%
“…static upright X-rays) are not effective for PD patients. Despite the detailed and, as described, difficult pre-OP diagnostics, the results of spinal surgery in PD patients are disappointing [4][5][6]. Yet in view of the increasing demand [1], there is an obvious gap of knowledge which must take considerations of further pre-operative aspects into account.…”
Section: Discussionmentioning
confidence: 99%
“…The stooped posture with flexing of the hips and knees as well as some degree of the trunk and neck is indeed one of the most noticeable signs of PD. As expected, the demand for spinal surgery in patients with PD increases rapidly, but the results are disappointing with failure rates of 25.8-100% [4][5][6][7]. It is already well understood that spinal deformity in PD is unique from degenerative deformity.…”
Section: Introductionmentioning
confidence: 85%
“…With the increasing prevalence of PD and the associated degenerative spinal conditions, the demand for spinal surgery in patients with PD increases rapidly. However, the results of spinal surgery for degenerative spinal conditions in patients with PD are disappointing with failure rates of 25.8-100% [8][9][10][11][12]. As an alternative treatment strategy for the underlying pathomechanism, some authors have described the influence of deep brain stimulation on PD-related postural abnormalities [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%